Development of fortified pasta products with reduced calorie content using Viburunum opulus L. meal - O. Ya. Kolman; G. V. Ivanova; E. O. Nikulina (Современная наука и инновации, 2024)
Enriched pasta products with reduced calorie content have been developed using Viburunum opulus L. meal. The cooking properties (cooking time until done, amount of absorbed water, percentage of dry matter) of pasta with different contents of Viburunum opulus L. meal powder in the recipe have been studied. The optimal dosage of meal powder has been determined. Viburunum opulus L. in the recipe, which amounted to 10% of the total amount of flour provided for in the recipe. These samples have the best quality indicators (organoleptic, physico-chemical). When analyzing their nutritional value, it was found that pasta with powder from Viburunum opulus L. meal, compared to the control sample, has a reduced calorie content (by 6.2%), and the amount of dietary fiber and proteins is higher by 71.43 and 3.7% respectively. The reduction in calorie content of products occurs due to a decrease in the content of fats in products with powder from Viburunum opulus L. meal by 15.4% and carbohydrates by 7.2% compared to products prepared according to the traditional recipe. Pasta with powder from Viburunum opulus L. meal can be classified as a fortified food product, since 100 g of ready-to-eat pasta satisfies the body's daily need for dietary fiber by 20.0%, and for proteins – 15.0%.